Determinants of business sustainability of women entrepreneurs - Adam, Amizahanum; Abdullah, Wan Razazila Wan; Maruhun, Enny Nurdin Sutan; Anwar, Irda Syahira Khair; Salin, Ahmad Saiful Azlin Puteh (International Journal of Management and Sustainability, 2024)
The issue of women in business or women in entrepreneurship has attracted much attention from researchers and practitioners in recent years, particularly in developing countries. This is due to the ability of women entrepreneurs to make a significant contribution to economic growth, country development, and escaping poverty. However, what determines their critical success factors as women entrepreneur is still under research. Thus, the purpose of this study is to examine the determinants of business sustainability specifically among women entrepreneurs. This study is original as it focuses on the business performance of women entrepreneurs during the pandemic crisis. This research used a market survey among women entrepreneurs as its research design and data collection. Seven constructs, comprised of six independent variables and one dependent variable, were used in the study. The independent variables are competency, marketing capability, financing resources, technology usage, motivation, and family support, while the dependent variable is business sustainability. This study used Resource-based View Theory (RBV) as its foundation for the research framework. This study finds that only family support influences business sustainability, while the other construct does not provide any conclusive evidence. This empirical study suggests that more support and training need to be provided by government agencies to ensure the survivability of women entrepreneurs in Malaysia.